Implementation of Problem-Based Learning in Enhancing Student Engagement and Learning Achievement in Islamic Religious Education for Children - Donna Ayu Suci Amanda; Alain Noor Ndzijia (Research Journal on Teacher Professional Development, 2026)
This study aims to explore the implementation of the Problem Based Learning (PBL) model as an innovative learning strategy in increasing student engagement and learning outcomes in the Asmaul Husna material in grade II of Katonsari 1 Public Elementary School, Central Java, Indonesia. This study used the Classroom Action Research (CAR) method which was implemented in two cycles. Data collection techniques included observation, tests, simple interviews, and documentation, while data validity was carried out through technical triangulation by comparing the results of observations, tests, interviews, and documentation. The results showed that in the pre-cycle stage, learning was still dominated by conventional methods so that students tended to be passive and less actively involved in the learning process. This condition resulted in low learning outcomes with classical completeness of 60% and an average score of 73.75, while student learning activities also only reached 60%. The application of the PBL model in the first cycle began to show an increase in student engagement in discussions and group activities, although the success indicators had not been optimally achieved. In cycle II, after improvements were made to learning through strengthening motivation, classroom management, and understanding of PBL steps, there was a significant increase in learning activities to 90% and classical completeness increased to 90% with an average score of 90. These findings indicate that the Problem Based Learning model is effective in improving the quality of the process and outcomes of Islamic Religious Education and Islamic Religious Education learning, both in cognitive, affective, and psychomotor aspects. This research contributes in providing an innovative problem-based learning model that is relevant to improving Islamic Religious Education learning at the elementary school level.